SUPPLY CHAIN DAN KINERJA PERUSAHAAN EVENT ORGANIZER DI INDONESIA - Edmund Kussumawara; Retno Hidayati (JURNAL STUDI MANAJEMEN ORGANISASI, 2018)
The growth of the tourism industry in Indonesia is on the rise, one of which is the growth of event organizers in various regions in Indonesia. However, the event organizer has the problems faced such as market competition, causing decreased income, which then results in not achieving sales targets and reducing the value of the company's assets over time. On the other hand, event organizers are required to be responsive to changes that occur in the market and are able to meet consumer demand. This study aimed the effect of supply chain agility and flexibility towards the firm performance with supply chain performance as a mediator. In this study, supply chain agility and flexibility as independent variable, supply chain performance as intervening variable, and firms performance as dependent variable.The population in this study are event organizers who were members of the Association of Indonesian Exhibition Companies (ASPERAPI) totaling 632. This study used a sample of 150 respondents through a questionnaire. All of them are event organizers who work on the government and BUMN sectors.This study tested by structural equation modeling (SEM). Which was later on developed into a theoritical model and procesed by a computing program AMOS 24.0. based on the result, the theoritical model has achived the cut off value of goodness of fit as follows, Chi-square = 67.509; probability = 0.236; CMIN / DF = 1.125; GFI = 0.931; AGFI = 0.896; TLI = 0.984; CFI = 0.988 RMSEA = 0.031, and degree of freedom (DF) = 60. Based on the results obtained, the model is declared feasible to use. The results of hypothesis testing show that supply chain performance has a positive effect on firm performance (0.54), supply chain agility does not affect firm performance (0.18), supply chain flexibility has a positive effect on firm performance (0.31), supply chain agility has a positive effect on supply chain performance (0.30), supply chain flexibility has a positive effect on supply chain performance (0.54).